1988
DOI: 10.1002/bms.1200150405
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral analysis of some derivatives andin vitro metabolites of steviol, the aglycone of the natural sweeteners, stevioside, rebaudioside a, and rubusoside

Abstract: Steviol (ent-13-hydroxykaur-16-en-19-oic acid), the aglycone of various plant-derived glycoside sweeteners consumed by human populations, is known to be mutagenic toward Salmonella tymphimurium strain TM677 when metabolically activated using a 9000 x g supernatant fraction derived from the liver of Aroclor 1254-pretreated rats. Mass spectral analysis of this diterpenoid and some analogs revealed characteristic patterns reflecting differential stereochemistry at the C/D rings and variations in the nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Compadre et al 13 reported that there are 22 possible derivatives of steviol and of these, only 15 have been studied by mass spectral analysis. We have developed a method to separate stevioside and its metabolites, namely, steviol-16,17α-epoxide, 15α-hydroxysteviol, steviolbioside, isosteviol, and steviol.…”
Section: Introductionmentioning
confidence: 99%
“…Compadre et al 13 reported that there are 22 possible derivatives of steviol and of these, only 15 have been studied by mass spectral analysis. We have developed a method to separate stevioside and its metabolites, namely, steviol-16,17α-epoxide, 15α-hydroxysteviol, steviolbioside, isosteviol, and steviol.…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenic effects of steviol, the aglycone of stevioside, and/or its metabolites were reported in the forward mutation assay using Salmonella typhimurium TM677 (12; concentrations tested: 0,0.1,0.5, 1,2.5 and 10 mg/ml; [14][15][16][17]. After metabolic activation, it was shown that so far unknown steviol metabolites caused mutations in Salmonella typhimurium TM677, i.e.…”
Section: Steviolmentioning
confidence: 99%
“…The mutagenicity of crude stevia extract, stevioside, and steviol have been reported (18)(19)(20)(21)(22)(23). Stevioside showed no mutagenicity in bacterial systems (18)(19)(20); however, its aglycone, steviol, was mutagenic after metabolic activation in the forward mutation assay using only Salmonella typhimurium TA677 (TM677) (21) but not mutagenic in the reverse mutation test using Salmmellka typhimurium TA100, TA98, TA102, or TA97.…”
Section: Mutagenicitymentioning
confidence: 99%
“…Stevioside showed no mutagenicity in bacterial systems (18)(19)(20); however, its aglycone, steviol, was mutagenic after metabolic activation in the forward mutation assay using only Salmonella typhimurium TA677 (TM677) (21) but not mutagenic in the reverse mutation test using Salmmellka typhimurium TA100, TA98, TA102, or TA97. When steviol was metabolically activated with S-9 from Aroclor 1254-pretreated rats, 15-oxosteviol was found to be the mutagenic product in the forward mutation assay (22). It was suggested (23) that this major, oxidized steviol was responsible for the indirect mutagenicity of steviol in TM677, probably by selectively inducing a deletion or insertion of more than one base pair, which cannot be found in strains of TA98, TA100, and TA102, which are regularly used in the Ames test.…”
Section: Mutagenicitymentioning
confidence: 99%